High performance high-density polyethylene/hydroxyapatite nanocomposites for load-bearing bone substitute: fabrication, in vitro and in vivo biocompatibility evaluation. (3rd May 2019) - Liu, Tong; Huang, Keqing; Li, Lengwan; Gu, Zhipeng; Liu, Xianhu; Peng, Xiangfang; Kuang, Tairong
Abstract: In this study, a strong and tough high-density polyethylene (HDPE)/hydroxyapatite (HA) nanocomposites with bone-analogues structure was successfully prepared via a simple dynamic-oscillation-shear processing method for biomedical application as bone substitute materials. Dynamic-oscillation-shear flow field was applied by self-made loop oscillatory push-pull molding (LOPPM) equipment. The LOPPM-processed HDPE/HA composites exhibited tremendous increase of tensile strength, modulus and toughness up to 95.1 MPa, 4.2 GPa, 58.4 kJ/m 2, respectively, which could be attributed to better dispersion of HA in HDPE matrix and highly ordered shish-kebab structure as evident from DSC, SEM, WAXD and SAXS studies. Meanwhile, the formed hierarchical structure not only showed bone-like structure, but also endowed composites with high strength, modulus and toughness, even close to the human cortical bone. Moreover, in vitro cell culture study was performed on NIH-3T3 fibroblast cells to evaluate the biocompatibility of the composites. The results showed that the produced bone substitutes exhibit good biocompatibility. Besides, using a rabbit calvarial defect model, in vivo testing has shown that a strong and stable interface is developed between the composites and the host bone. Overall, we present a facile and green strategy to generate polymer composites with high strength and toughness and the produced LOPPM-processed HDPE/HA polymer nanocomposites have a great potential for use as load-bearing bone substitute in biomedical application.